Workplace harassment: The leadership factor. Issue 2 (March 2021) - Adams, Lisa; Bryan, Venise
Healthcare professionals are in the business of providing care and compassion. It is ironic that healthcare has the highest rate of workplace harassment. Although harassment comes from people of various positions, its existence in healthcare fractures the intention and values that guide its mission. When mental health is compromised, mistakes happen. Healthcare professionals take the health/life of others into their care; distractions and fear from being bullied compromise that care. Health leaders are in a strategic position to address workplace harassment and bullying. Failing to do so results in complacency, jeopardizes our patients, tarnishes the organization, and damages society as a whole. It is a cost that all will pay dearly to remedy, unless it is addressed, enforced with standards, and taken to task for the better health of all.